Pemberdayaan Kader PKK dengan Inovasi Gerakan Sayang Ibu sebagai Upaya Mencegah Stunting di Kelurahan Brotonegaran Ponorogo - Isnatin, Umi; Nurfadila, Agustin Rani; Pibriyanti, Kartika; Ahdi, Istaufal; Nugraha, Rasyid Ridla; Burhanudin, Burhanudin (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Stunting is a condition of failure to grow in toddlers due to chronic malnutrition, repeated infections, and inadequate parenting in the first 1000 days of life. The prevalence of nutritional status toddler in Brotonegaran Village is 5.08% and one of the efforts to prevent stunting with food security. This service activity is carried out in synergy with the government to support the PKK, namely health. The purpose of this activity is to empower PKK cadres through counseling and training, as well as mentoring with Gerakan Sayang Ibu. Method: The activity partner is the PKK cadre group of Brotonegaran Village. The number of participants was 25 people. The methods used are counseling, training, and mentoring. Results: 25 PKK cadres were participating in a series of empowerment activities, including an FGD with the theme of empowering PKK in raising laying hens to suppress stunting which was attended by the village head and representatives of the local health center. The first counselor is about improving the quality of free-range chicken production and assistance in raising free-range chickens, the second counselor is about nutritional needs in the first 1000 days of life. Asih Asuh distributes free-range chicken eggs as a high-protein food to meet the needs of stunting-prone risk groups. Conclusion: The empowerment of PKK cadres through FGD activities, training counseling, and foster care for the distribution of free-range chicken eggs, increased by 30% related to the knowledge, experience, and concern of PKK cadres as family companions in the community.